GE_GERICHTE A/320/2023 vom 6. Dezember 2023 - GE Cour de justice (2023)
DOMAINE PUBLIC;TERRASSE DE RESTAURANT;QUALITÉ POUR RECOURIR;TIERS | LPA.60.al1.letb; RTEP.20.al2; RTEP.27; LRoutes.77ss; LRoutes.85ss